(untitled) (International Journal of Environmental Sciences, 2025)
Disasters and environmental degradation are generally considered parts of non-traditional threat to National Security. India by virtue of its geo-climatic and socio-economic conditions is one of the five most affected countries in the world in terms of number of deaths and due to various natural disasters that make it vulnerable. However, India has also transitioned to a position of being an important ‘provider of assistance in international disasters.’ Since India has a progressive and forward looking development agenda of inclusive growth, which is getting impacted by disasters, disaster risk reduction has emerged as a high priority focus area in India’s national policy framework. In this perspective, the paper examines the ‘vulnerability’ aspect of India in the larger context of disaster management in India’s national security.